ORGANIZING E-LEARNING OF PHYSICS – EDUCATIONAL ACTIVITIES IN OUT-OF-SCHOOL HOURS - Voronkin, О.С. (Journal of Information Technologies in Education (ITE), 2012)
Experience of organizing pedagogical experiment – an open distance course «Introduction in acoustics» is analyzed in this paper.